2017
DOI: 10.1002/ange.201704676
|View full text |Cite
|
Sign up to set email alerts
|

Pentagon‐Embedded Cycloarylenes with Cylindrical Shapes

Abstract: Figure 4. Non-hexagon networks of sp 2 -carbon atoms. a) Basic transformations of graphenes for the construction of cylinder-shaped haeckelite congeners. Pentagon units are shown in purple, and heptagons are shown in green. Stone-Wales-type and ad-dimert ransformations were previously reported, [11,13] and their combination was examined in this study.b )Basic networks of new haeckelite congeners( 3 and 4)c onstructed from [3]CR molecules by addimer/Stone-Wales transformations. Molecular models (left), chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Bond length, bond angle, and torsion angle among carbon atoms are nearly constant on the basis of their hybrid orbitals. On the other hand, unusual geometrical parameters have been reported for highly strained molecules, such as sterically congested and/or curved polycyclic aromatic hydrocarbons [1][2][3][4][5][6][7][8] as well as cyclic p-conjugated molecules, including cycloparaphenylenes, [9][10][11][12][13][14][15][16][17] which are endowed with special properties that the ordinary hydrocarbons do not have. In these novel aromatic compounds, the pyramidalization of C sp 2 carbons and the bond and torsion angles that deviate from the standard values are responsible for the formation of distorted structures.…”
Section: Introductionmentioning
confidence: 99%
“…Bond length, bond angle, and torsion angle among carbon atoms are nearly constant on the basis of their hybrid orbitals. On the other hand, unusual geometrical parameters have been reported for highly strained molecules, such as sterically congested and/or curved polycyclic aromatic hydrocarbons [1][2][3][4][5][6][7][8] as well as cyclic p-conjugated molecules, including cycloparaphenylenes, [9][10][11][12][13][14][15][16][17] which are endowed with special properties that the ordinary hydrocarbons do not have. In these novel aromatic compounds, the pyramidalization of C sp 2 carbons and the bond and torsion angles that deviate from the standard values are responsible for the formation of distorted structures.…”
Section: Introductionmentioning
confidence: 99%
“…22,48 Theoretical calculations revealed that the free energy of activation for the racemisation of the model structure (1c) is as high as 29.2 kcal/mol (Fig. 4b), which lies between those of [5]helicene and [6]helicene (24.6 and 36.2 kcal/mol, respectively) (Fig. 4c).…”
Section: Resultsmentioning
confidence: 96%
“…Accordingly, much effort has been devoted towards synthesising and elucidating the properties of topologically diverse graphene nanostructures, whose hexagonal rings are fused in different patterns. [1][2][3][4] Researchers have also been interested in introducing non-hexagonal rings such as pentagons, [5][6][7] heptagons, [8][9][10] or octagons 11 into -conjugation systems to achieve unique optical, electronic, and structural properties, distinct from those of -systems composed of only hexagonal units.…”
mentioning
confidence: 99%
“…This was the first report of a chiral resolution of a conjugated nanohoop by chiral derivatization with an enantiopure reagent. Usually, preparative chiral HPLC is employed to separate single enantiomers of chiral nanohoops, 53 54 56 , 69 70 71 which is costly and time-intensive, and only permits the isolation of small quantities of enantiopure hoops. In contrast, the resolution of enantiomers by chiral derivatization of diketo[6]CPP 10 can be easily upscaled and adapted to other hoop sizes n to provide access to enantiopure chiral diketo[ n ]CPPs.…”
Section: Synthesis Of Dbp-based Nanohoopsmentioning
confidence: 99%